Competing processes of cell death and recovery of function following ischemic preconditioning in the gerbil - Dooley, Paul James, 1972- (St. John's, NF : [s.n.], 1997)
Thesis (M.Sc.)--Memorial University of Newfoundland, Faculty of Medicine, 1997. Medicine Bibliography: leaves 57-78 In process